The Role Of Tanjung Suara Makarti Radio (Tasma Fm) As A Dakwah Media To Grow Islam In The Nusantara - Sutamaji Sutamaji; Miftachul Aula (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2023)
Preaching via radio is an appropriate means of conveying da'wah messages. One of the radio stations that focuses on segmenting its programs containing da'wah in Nganjuk Regency is Radio Tasma (Tanjung Suara Makarti) 99.04 FM in Tanjunganom District. The essence of the problem that the author will analyze in this research is how to plan the da'wah media program as well as the program model and evaluation of Islamic studies da'wah at PT. Radio Tanjung Suara Makarti (Tasma Fm) Nganjuk. This research uses descriptive qualitative research and uses inductive analysis. From the results of the research carried out by the author and outlined above, the following conclusions can be drawn: (1) Planning for the Islamic Studies Da'wah program. In this case it is linked to the topic that will be chosen. Then in the planning part the crew on duty will be determined according to their duties, such as producer, event director, moderator, announcer, and others. (2) The Islamic Studies Program Model is a daily program that airs from five to six in the morning from Monday to Sunday. (3) Evaluation of the Da'wah Media Program for Grounding Islam in the Archipelago can be done in two ways, namely evaluation of the planning and evaluation of the program model.